2001
DOI: 10.1103/physreve.63.046311
|View full text |Cite
|
Sign up to set email alerts
|

Rarefaction shock wave:  Formation under short pulse laser ablation of solids

Abstract: We investigate formation, dynamics, and decay of the rarefaction shock wave under the conditions of ultrashort pulse laser ablation of solids. On the basis of the Euler equation and the van der Waals equation, we consider the planar and spherical expansion into vacuum matter heated instantaneously above the thermodynamic critical temperature. When the expansion occurs along an abnormal adiabat, in a part of which ( partial differential(2)p/ partial differentialv(2))/(S)<0, a rarefaction shock wave moving towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…It has been shown that negative nonlinearity can be realized for materials with different EOS [24]. Recently [15] we have shown that, for the three-parametric modification of the van der Waals EOS [25,26] which accurately describes a wide variety of substances, the RSW behaves differently as compared to the case with the classic van der Waals EOS [2], which is worthy of detailed study.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…It has been shown that negative nonlinearity can be realized for materials with different EOS [24]. Recently [15] we have shown that, for the three-parametric modification of the van der Waals EOS [25,26] which accurately describes a wide variety of substances, the RSW behaves differently as compared to the case with the classic van der Waals EOS [2], which is worthy of detailed study.…”
mentioning
confidence: 94%
“…Recently it has been shown that, under ultrashort-pulse laser ablation of solids, the rarefaction shock wave (RSW) can be formed in laser-induced plumes [1,2]. An intriguing picture of the formation of a compressed layer in the ablation products expanding in a vacuum has been revealed after RSW reflection from a nonvaporized target surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ͒ As predicted by Zel'dovich, 2 analyzed by Thompson,3,4 and clarified experimentally by Borisov, 5 an expansion shock wave can be generated in the vicinity of the "liquid-vapor" critical point, or in some porous solids undergoing a phase transition at high pressures, etc. [6][7][8][9][10] For example, near the liquid-vapor critical point, the value ‫ץ͑‬ 2 p / ‫ץ‬v 2 ͒ s becomes negative for a substance with a reasonably high specific heat c v ͑where p, v, and s represent the pressure, specific volume, and entropy, respectively͒ and, therefore, expansion shock waves can be generated under such specific conditions. 9 In a "gaseous" medium corresponding to normal fluids, however, the value ‫ץ͑‬ 2 p / ‫ץ‬v 2 ͒ s is positive.…”
Section: Introductionmentioning
confidence: 99%